Pembelajaran Agama Islam Pada Anak Usia Dasar Di Tinjau Dari Pekerjaan Orang Tua Di Tadika Darulmuttakin Yaring Patani Selatan Thailand - Mareena Adam; Yurmaini Yurmaini; Ade Rahman Matondang (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
In educating children, parents must be good according to the teachings of the Prophet Muhammad SAW where children are a sense of gratitude and a mandate that must be guarded and raised with affection. As the first educator in the family, parents have a significant influence on their children. In increasing children's motivation to learn religion, children need support and attention from parents in the education process. The question of this research is how Islamic Religious Learning in Elementary School Children is reviewed from the Work of Parents at Tadika Darulmuttakin Yaring Patani Selatan Thailand. The purpose of this study was to determine whether parents had given good attention in improving the character of religious learners to their children. This type of research is qualitative using a qualitative descriptive approach. The data collection techniques used were interview methods, observation methods and documentation methods. The data sources for this study were the principal, teachers, parents and children's learning. The location of the study was in Cha-oq Yaring Patani Selatan Thailand. The validity of the data was obtained from the triangulation technique which was achieved by comparing the data from the interview and the results of observations. Furthermore, the steps used in analyzing the first data were data reduction, display and finally conclusions. The results of this study indicate that Tadika Darulmuttakin Yaring Patani Selatan Thailand. take how to learn Islamic religion in ways namely; 1) provide education in the language of noble morals to elementary age children through curriculum, methods and activities provided by TADIKA; 2) developing personality and Islamic values which the teacher plays a major role in developing through programs, both core and additional, technical delivery of material, or by way of dress and appearance.